Functions of natural sciences and the functions of social sciences - Cichocki, Ryszard (Humaniora. Czasopismo Internetowe, 2020)
The main point of this article hinges upon the assumption that one of the key factors distinguishing between applied natural sciences and applied social sciences is a difference of the functions used by them for instrumental control over the environment. When it comes to natural sciences there is one function with relatively homogenous set of employed applications, when it comes to the social sciences it is a set of six functions which comprise a very large and heterogenous set of practical applications. Basic natural sciences facilitate the needs of applied natural sciences for basic knowledge which then allow for effectively executing the following practical uses: monitoring and oversight, designing and constructing, optimisation and development of complex technologies. Where applied social sciences implements a vastly larger range of practical applications as apart from those that are similar to the natural sciences they also have our full range of specific uses which are associated with the above discussed functions: indoctrination and emancipation, steering consumer behaviour and the shaping of consumer competence that allows for defending against such steering, triggering political mobilisation and facilitating autonomous civic competence, designing social promotion campaigns and shaping critical attitudes with respect to marketing activities.